Touching with Words: On Description and its Images - Cabello Padial, Gabriel (Escritura e Imagen, 2025)
In this article, we aim to approach description as a transformative activity operating on different levels. To do so, we will examine three examples. The first two can be associated with the rhetorical figure of hypotyposis, where the text produces images that extend beyond itself; the third can be linked to ekphrasis, where the text positions itself on this side of a perceived image that it describes. The first case is a theoretical text taken from La poesía, la música y el silencio (De Mallarmé a Wittgenstein) (1994) by Juan Carlos Rodríguez, in which the description of a scene —one that is, as such, nonexistent— renders a critical problem perceptible. The second is Borges’s poem «Historia de la noche» (1977), where the effect of literature on visual perception is thematized according to the model of dream —as he understood it. The third is Ángel González’s essay on Manet, «La pintura se complica» (2003), where description becomes the instrument that allows —as Daniel Arasse explicitly proposed— the transformation of some of the critical categories that had defined the narrative about modern art. There is also a connecting thread which connects the three examples: the porosity of a reality whose fissures are filled with images.
Keywords: Description; images; dream; Juan Carlos Rodríguez; Borges; Ángel González; Mallarmé; Manet